The Advisory Board: A Department Chair's Best Friend - Jerry G. Holt (Academic Chairpersons Conference Proceedings, 2016)
Does a department need an Advisory Board? The English Department at Purdue's North Central campus has found that its Board may be the best thing that's ever happened to it. This presentation explores the community links that can be formed through such a Board--and the opportunities for students that ensue.
Keywords: Community; Internsehips; Partnerships; Service; Students